Analisis Tingkat Kesehatan PT. Bank Aceh Syariah Dengan Menggunakan Metode RGEC - Budianto Budianto (Jurnal REKOMEN (Riset Ekonomi Manajemen), 2020)
This study aims to analyze the level of health at the Aceh Syariah Bank in the 2014-2018 period. This study uses a quantitative descriptive approach through the RGEC (Risk Profile, Good Corporate Governance, Earnings, and Capital) methods. The data collection method uses documentation techniques on published financial reports (secondary data), and analyzes based on BI Regulation No.13/1/PBI/2011 and BI Circular Letter No. No.13/24/DPNP/2011 concerning Assessment of Commercial Bank Soundness Levels, as well as OJK Regulation No. 08/POJK.03/2014 and OJK Circular Letter No.10/SEOJK.03/2014 concerning Evaluation of the Health Levels of Sharia Commercial Banks and Units Sharia Business. The results of this study indicate that the Bank of Aceh Syariah during the 2014-2018 period as a whole was in good health. This is indicated by the Risk Profile (NPF, FDR), GCG, Earnings (ROA, BOPO) and Capital (CAR) from 2014-2016 with a composite rating of 2 (healthy), while in 2017-2018 with a composite rating of 3 (quite healthy).